2019
DOI: 10.1007/s10120-018-00918-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of MLH1 and PD-L1 expression for prognosis and response to preoperative chemotherapy in gastric cancer

Abstract: Background Microsatellite instability (MSI) and programmed death-ligand 1 (PD-L1) are candidate predictors for the response to immune checkpoint inhibitors, and may predict chemotherapy sensitivity. We investigated the simultaneous expression of mutL homolog 1 (MLH1), a mismatch repair gene, and PD-L1 in gastric cancers. Methods We examined MLH1 and PD-L1 expression in surgical specimens from 285 gastric cancer patients treated with or without preoperative chemotherapy, and assessed the relation between expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 33 publications
2
51
1
1
Order By: Relevance
“…Thus, the management of GC patients with HBV infection is still a clinical challenge. Hashimoto et al previously reported that the expression of PD‐L1 and MLH1 were negatively correlated in another GC study. Here, we found PD‐L1 seemed lost and MLH1 were often retained in HBV carriers GC patients.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, the management of GC patients with HBV infection is still a clinical challenge. Hashimoto et al previously reported that the expression of PD‐L1 and MLH1 were negatively correlated in another GC study. Here, we found PD‐L1 seemed lost and MLH1 were often retained in HBV carriers GC patients.…”
Section: Discussionmentioning
confidence: 78%
“…In a recent systematic review MSI-H was found to be associated with female sex, older age, intestinal Laurén histological type, mid/lower gastric location, lack of lymph node metastases and TNM stage I-II, but not with ethnicity [33]. Between 6 and 24% of resected gastroesophageal adenocarcinomas are reported to be MSI-H [20,[34][35][36][37][38][39], and this may even mount up to 48% in patients of 85 years and older [40]. However, the percentage sharply drops to less than 10% in patients with synchronous metastatic disease [41], and less than 5% in a beyond-second line treatment setting [19].…”
Section: Prevalence Of Msi In Gastroesophageal Adenocarcinomamentioning
confidence: 99%
“…In a study aiming at determining the predictive value of MLH1 and PD‐L1 expression for prognosis and response to preoperative chemotherapy in gastric cancer, Hashimoto et al 26 demonstrated that patients with resectable MSI GC, due to loss of mutL homolog 1 (MHL1), exhibit a good prognosis and negative response to fluorouracil‐based chemotherapy. In a similar study, Di Bartolomeo et al 27 showed that MSI status was independently associated with increased disease‐free survival and overall survival in GC patients randomised for an intensive sequential chemotherapy regimen vs fluorouracil/leucovorin monotherapy as adjuvant treatment.…”
Section: Response To Immunotherapymentioning
confidence: 99%